Dispersion in Crystal Structures of 1-Chloro-3-aryl-5-trihalomethyl-1λ4,2,4,6-thiatriazines: Towards an Understanding of the Supramolecular Organization of Covalent Thiazyl Chlorides - Kondage, Savini Suduweli; Roemmele, Tracey L.; Boeré, René T. (Synlett, 2023)
The syntheses of five new 1-chloro-3-aryl-5-trichloromethyl-1λ4,2,4,6-thiatriazines, aryl = 4-R-C6H4- (R = CH3O, CH3, H, Cl and CF3), are reported with full characterization. Single-crystal X-ray diffraction structure determinations on all, as well as the 5-CF3 analogue which also has R = CF3, with models produced by Hirshfeld atom refinement, produced high-accuracy structures. All six exemplars form lateral dimers with short contacts that define a centrosymmetric {δ+S···Nδ−}2 motif, with interaction distances from 3.0473(9) to 3.422(3) Å, which do not vary in an expected manner with R. Normal population analysis charges computed by B3LYP-D3/6-311++G(d,p) DFT methods show small variations, and entirely as expected from the inductive effects of R. Gas-phase minimization of the dimers with M06-2X/aug-cc-pVDZ or B3LYP-D3/6-311++G(d,p) methods, with full counterpoise correction, replicate the experimental geometries for the 5-CF3, the 5-CCl3/CH3OC6H4 and the 5-CCl3/CH3C6H4 experimental structures, but diverge for other CCl3 exemplars. Interaction energies are more than double those computed for [(HC)2N2S]2. Using a geometry-optimized model with H in place of CX3, the interaction energy reduces to a very realistic –22 to –24 kJ/mol for just the {δ+S···Nδ−}2 motif, suggesting that CX3 interactions contribute 21% (CF3) to 37% (CCl3) of the total.
Keywords: chlorothiatriazine; thiazyl; supramolecular interaction; dispersion correction; counterpoise correction; density functional theory; X-ray crystallography; molecular squares